Efficacy of transscleral Nd:YAG laser cyclophotocoagulation and changes in blood circulation in the eye of patients with absolute glaucoma - P. P. Chechin; O.V. Guzun; N. I. Khramenko; O. A. Peretyagin (Ukrainian Society of Ophthalmologists, 2018)
Background. Absolute glaucoma is a disease which is caused by a range of different factors and which refers to a most severe ophthalmic pathology. Treatment of absolute glaucoma is often insufficient to manage pain and to decrease intraocular pressure. The purpose. To study changes in ocular hemodinamics and efficacy of transscleral (TS) Nd-YAG laser cyclophotocoagulation (CPC) in patients with absolute glaucoma. Material and Methods. We followed-up 30 patients (32 eyes) with absolute glaucoma; patients' age averaged 62.5 (SD, 2.09); 19 males (63%) and 11 females (37%). Baseline best corrected visual acuity (BCVA) averaged 0.011 (SD 0.018): BCVA=0.001-0.06 in 15 eyes (47%); BCVA=light perception (correct) in 5 eyes; BCVA=no light perception (incorrect) in 2 eyes; BCVA=0 in 12 eyes. A baseline IOP level averaged 38.2 (SD 5.05) mmHg ranging from 29.0 to 47.0 mmHg. A treatment course included three TS CPC sessions performed by Nd:YAG laser (λ=1.06 μm, I=0.8 J) every other day. TS CPC was performed concentrically in full circle (360°) in two rows, at 1.5-2.0 mm from the surgical limbus. A schedule of antihypertensive instillations was not changed. Additionally, a course of anti-inflammatory therapy was prescribed (indometacin, 0.1%, 4 times a day for a month). Results and Discussion. TS CPC of the ciliary body resulted in pain management in all patients (100%). The IOP level was significantly decreased compared to baseline: by 32%, immediately after TS CPC of the ciliary body and by 23% at 3 months after TS CPC, to 26 (SD 2.85) mmHg and 29.4 (SD 5.44) mmHg, respectively. Visual function remained the same after a treatment course. RQ blood circulation decreased after a treatment course at average by 34%, or to 2.3 (1.46) ‰ (р=0.00002). Vascular tone improved after TS CPC in 11%, 25.0 (SD 1.29)‰. The correlation analysis revealed a direct relationship between: the number of applications performed and a decrease of IOP (r=0.45), (р<0.05) as well as postoperative blood circulation (r=0.36), (р<0.05). There was also noted a significant correlation relationship (r=0.42), (р<0.05) between a decrease of an IOP level and a decrease of volume blood circulation of the eye after TS CPC of the ciliary body. Age and gender had no significant correlation relationship with IOP changes. TS CPC of the ciliary body did not achieve a desired effect in 8 patients (25%), which required a repeat course after three months. Conclusions. TS CPC of the ciliary body in patients with absolute glaucoma decreases IOP at average by 32% immediately after surgery and by 23% at 3 months after TS CPC. TS CPC of the ciliary body in patients with absolute glaucoma decreases volume blood circulation in the vascular pool of the ciliary body by 34% and reduces tonic properties of ciliary vessels by 11 %. TS CPC of the ciliary body is a successful organ-sparing treatment for patients with absolute glaucoma and has an apparent analgesic endpoint.